Unfolding the Future of the Long War Motivations, Prospects, and Implications for the U.S. Army - Pernin, Christopher G. (RAND Corporation, 2008)
The United States is currently engaged in a military effort that has been characterized as the "long war." This study explores the concept of long war and identifies ways in which it might unfold as well as the implications for the Army and the U.S. military more generally. This report uses the generation of either "trajectories" or alternative paths in which the long war might unfold to explore the implications for the U.S. military.